2007
DOI: 10.1071/py07034
|View full text |Cite
|
Sign up to set email alerts
|

Community Capacity Building for Health Promotion: Lessons from a Regional Australian Initiative

Abstract: This paper discusses a health promotion intervention that sets out to develop local capacity to address chronic disease risk factors in a remote Australian community. Community focus groups, and researcher and community discussions, aimed to determine the community's health concerns and build a partnership for community action. The journey from conception to reality was difficult for a number of reasons that are described here. Despite these difficulties, a range of outcomes included the establishment of an or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…However, all studies were included in this review because of the paucity of research on this topic. Six projects in this review were conducted or reported by Laverack (Laverack 2003, 2005, 2007, Laverack & Jones 2003, Laverack & Thangphet 2009) while the remaining four were conducted by other researchers (Fleming et al. 2007, Olney et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, all studies were included in this review because of the paucity of research on this topic. Six projects in this review were conducted or reported by Laverack (Laverack 2003, 2005, 2007, Laverack & Jones 2003, Laverack & Thangphet 2009) while the remaining four were conducted by other researchers (Fleming et al. 2007, Olney et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2007) chose to conduct a project in Hispanic communities along the Texas‐Mexico border due to the fact that some communities in this area encountered the lowest levels of income, educational level and access to health services. Similarly, Fleming et al. (2007) developed a project to reduce the risks of chronic disease that was based in a remote community where the unemployment rate was increasing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations